Evolução tectônica do domo de Monte Alegre – PA, Borda Norte da Bacia do Amazonas. - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2025)
This research presents an integrated structural analysis of the Monte Alegre Dome, located in the central-eastern portion of the Amazonas Basin, with the aim of understanding its genesis and tectonic evolution. The research combined field data, seismic profiles, exploration wells, and structural restorations, focusing on the relationships between folding and faulting in a thick-skinned basement tectonics model. Additionally, this research presents the results of geological mapping at 1:25,000, integrating hundreds of structural data, including bedding, folds, and faults. The mapped lithostratigraphic units include the Ererê, Barreirinhas, Curiri, Oriximiná, Faro, Monte Alegre, and Alter do Chão formations, with thicknesses ranging from 100 to 400 meters. Mapping reveals that the Monte Alegre Dome is characterized by a semicircular arrangement of strata, with gentle dips of 5° to 15°. In the eastern portion of the Dome, the layers closest to the fault have steep dips of 45° to 75°. These dips are interrupted by a significant compressional fault in the eastern and southwestern portions. Most of the deformation is concentrated along the Itauajuri Fault, interpreted as a high-angle reverse fault, whose movement generated asymmetric folds due to normal drag. The restored models revealed shortenings exceeding 7 km in selected sections near the greatest shortening trend, with fault slip of up to 1,840 meters, in addition to uplift-associated erosion estimated at approximately 1,600 meters. Multiscale structural analysis and comparison with classical models indicate that the dome's geometry results from deep crustal compression, possibly activated in the Miocene, in response to intraplate readjustment associated with the Quechua III phase of the Andean tectonics and the Xingu Diastrophism. Using quantitative data and a modern structural approach, the results suggest a new interpretation for the dome's origin as the result of a single-phase compressional deformation event, strongly controlled by reverse faults, and reinforce the presence of positive tectonics in the Amazonas Basin.
Keywords: Restauração estrutural; Deformação; Geologia estrutural; Mapeamento geológico; Tectônica compressional; CNPQ:: CIÊNCIAS EXATAS E DA TERRA